1, 2, 3-Triazolyl-4-oxoquinolines: A feasible beginning for promising chemical structures to inhibit oseltamivir-resistant influenza A and B viruses. Issue 24 (15th December 2015) - Boechat, Fernanda da C.S.; Sacramento, Carolina Q.; Cunha, Anna C.; Sagrillo, Fernanda S.; Nogueira, Christiane M.; Fintelman-Rodrigues, Natalia; Santos-Filho, Osvaldo; Riscado, Cecília S.; Forezi, Luana da S.M.; Faro, Letícia V.; Brozeguini, Leonardo; Marques, Isakelly P.; et al.
Graphical abstract: We described the synthesis of a new congener series of 1, 2, 3-triazolyl-4-oxoquinolines and evaluated their ability to inhibit oseltamivir (OST)-resistant influenza strains. Oxoquinoline derivative1i was the most potent compound within this series, inhibiting 94% of wild-type (WT) influenza neuraminidase (NA) activity. Compound1i inhibited influenza virus replication with an EC50 of 0.2 μM with less cytotoxicity than OST, and also inhibited different OST-resistant NAs. These results suggest that 1, 2, 3-triazolyl-4-oxoquinolines represent promising lead molecules for further anti-influenza drug design. Abstract: We described the synthesis of a new congener series of 1, 2, 3-triazolyl-4-oxoquinolines and evaluated their ability to inhibit oseltamivir (OST)-resistant influenza strains. Oxoquinoline derivative1i was the most potent compound within this series, inhibiting 94% of wild-type (WT) influenza neuraminidase (NA) activity. Compound1i inhibited influenza virus replication with an EC50 of 0.2 μM with less cytotoxicity than OST, and also inhibited different OST-resistant NAs. These results suggest that 1, 2, 3-triazolyl-4-oxoquinolines represent promising lead molecules for further anti-influenza drug design.